Public trust and genomic medicine in Canada and the UK - Savić-Kallesøe, S; Middleton, A; Milne, R (F1000Research, 2021)
Background: Genomic medicine could improve precise risk stratification, early prevention, and personalised treatment across a broad spectrum of disease. As this reality approaches, questions on the importance of public trust arise. The success of genomic medicine initiatives is influenced by the public’s trust and willingness to engage. Specific social actors influential in the public's trust have been identified by the “Your DNA, Your Say” study, including doctors, researchers, and governments. This paper aims to identify and examine which specific social actors, if any, in Canada and the United Kingdom (UK) are the most trustworthy and influential to engage the public in genomic medicine research. Methods: Using data from the ‘Your DNA, Your Say’ study, logistic regression models and Pearson’s chi-square tests were conducted to explore trust in social actors across Canada and the UK. Results: The results demonstrate Canada and the UK significantly differ in public trust and willingness to donate. Non-profit researchers, domestic doctors, and personal doctors were identified to be the most influential and trustworthy social actors in Canada and the UK. Conclusions: The comparative results indicate that both countries would benefit from engaging the public through doctors and non-profit researchers. The UK could additionally support public trust by engaging with the public through the National Health Service. However, the results suggest that whilst public trust is significant, it may be neither necessary nor sufficient in influencing willingness to donate. Future research could do well to investigate how the importance of public trust compares in countries with lower public trust.